Factors Influencing Investment Decisions Among Generation Z Students at Universities on Bengkalis Island - Reni Agusti; Nur Anita (Universitas KH. Abdul Chalim Mojokerto, 2025)
Students' interest in investing is growing, but the quality of investment decisions is still influenced by various factors. This study aims to analyze the influence of investment knowledge, investment motivation, financial behavior, and financial literacy on student investment decisions at three universities on Bengkalis Island. Data was collected through Google Form questionnaires and live questionnaires, with a total of 122 respondents. The analysis methods used were descriptive statistics and multiple linear regression. The results showed that investment knowledge had a significant effect on investment decisions (t = 3,685; Sig = 0.000; β = 0,250). Financial behavior also had a significant effect (t = 3,294; Sig = 0.001; β = 0.209), as well as financial literacy which was the most dominant variable (t = 5.971; Sig = 0.000; β = 0,550). However, investment motivation had no significant effect (t = –1,687; Sig = 0.094). In conclusion, the ability to understand finances and the way students manage their money has been proven to have more influence on investment decisions than just motivation. Further research is suggested to add variables related to financial behavior and expand populations and locations to make the results more comprehensive.